A review of the spider genus Iberina (Araneae, Hahniidae) - Růžička, Vlastimil (Zootaxa, 2022)
The spider genus Iberina has been reviewed and an updated description of the genus is presented. A key to the genera of the subfamily Hahniinae and to the species of Iberina is given. The genus Iberina now includes five species. The following new synonymy is proposed: Iberina caeca Georgescu & Sarbu, 1992 = Iberina microphthalma (Snazell & Duffey, 1980) new synonymy. Iberina ljovuschkini Pichka, 1965 is only known from females. It is considered to be a species inquirenda and its name declared a nomen dubium.